Transcriptome Analysis of the Sm-Mediated Hypersensitive Response to Stemphylium lycopersici in Tomato - Yang, Huanhuan; Zhao, Tingting; Jiang, Jingbin; Chen, Xiuling; Zhang, He; Liu, Guan; Zhang, Dongye; Du, Chong; Wang, Songbo; Xu, Xiangyang; Li, Jingfu (Frontiers in Plant Science, 2017)
Gray leaf spot disease caused by Stemphylium lycopersici is a major disease in cultivated tomato plants and threatens tomato-growing areas worldwide. Sm is a single dominant gene that confers resistance to tomato gray leaf spot disease agent. However, the underlying molecular mechanism remains unclear. Here, resistant (cv. Motelle, containing the Sm gene) and susceptible (cv. Moneymaker) plants were inoculated with virulent Stemphylium lycopersici isolate at a time point at which both cultivars showed a strong response to S. lycopersici infection. Transcriptome analyses were performed in both cultivars using RNA-seq. The number of differentially expressed genes (DEGs) was higher in Motelle than Moneymaker. Functional classification revealed that most DEGs were involved in plant–pathogen interactions, plant hormone signal transduction, regulation of autophagy, glycerophospholipid metabolism, and α-linolenic acid metabolism. Moreover, the genes that were significantly up-regulated in Sm tomatoes were involved in plant–pathogen interaction pathways. A total of 26 genes were selected for confirmation of differentially expressed levels by quantitative real-time PCR. This knowledge will yield new insights into the molecular mechanism of Sm responses to S. lycopersici infection.